Investigating the Effect of Lumbar Spinal Stenosis (LSS) Surgery on Sexual Function in Male Patients over 50 Years - Reza Fatahian; Saeed Gharooee Ahangar; Mehran Bahrami Bukani; Masoud Sadeghi; Annette B. Brühl; Serge Brand (Medicina)
Background and Objectives: Lumbar spinal stenosis (LSS) is a leading cause of back surgery in elderly individuals. Additionally, LSS can result in buttock pain; abnormal sensations; or even loss of sensation in the thighs, feet, legs, and buttocks, as well as potential loss of bowel and bladder control. As a further consequence, sexual activity is impaired. However, there is limited information on sexual function in patients undergoing LSS surgery, in general, and among male patients, in specific. Accordingly, the aim of this study was to investigate the effect of LSS surgery on sexual function in male patients over 50 years. Materials and Methods: Participants were fifty male patients with LSS aged 50 years and older who underwent LSS surgery at the Imam Reza Hospital in Kermanshah from March 2024 to the end of 2024. To assess sexual performance over time, participants completed the International Index of Erectile Function (IIEF-15) questionnaire both before LSS surgery and six months after LSS surgery. For pre–post comparison, we used paired t-tests. Results: Compared to the pre-surgery stage, six-month post-surgery improvements were erectile function (+21%; Cohen’s d: 1.40), orgasmic function (+35.1%; Cohen’s d: 1.49), sexual desire (+27.3%; Cohen’s d: 1.48), intercourse satisfaction (+14% Cohen’s d: 0.77), overall satisfaction (+34.6% Cohen’s d: 1.74), and overall sexual function (+25.3%; Cohen’s d: 1.48). Conclusions: Among a sample of male patients aged 50 years and older, LSS surgery improved all dimensions of sexual satisfaction, including orgasmic, erectile, and sexual functions; sexual desire; intercourse satisfaction; and overall satisfaction. Medical doctors treating males with LSS might consider informing their patients about the favorable effects of LSS surgery on sexual life and sexual satisfaction.